Impact of Smoking on Hematological Parameters Among Adult Males in Western Tripoli: A Cross-Sectional Study - Aeshah A. Altayf, (AlQalam Journal of Medical and Applied Sciences, 2019)
Background and aims. Smoking is a major modifiable risk factor that can induce systemic alterations, including changes in hematological parameters. Understanding these changes is crucial for early detection of physiological stress and potential disease risk among smokers. This study aimed to assess the effect of smoking on hematological parameters among adult males. Methods: A cross-sectional descriptive study was conducted among 100 adult males in western Tripoli, Libya, including 50 smokers and 50 non-smokers. Hematological parameters were measured and compared between groups using an independent samples t-test (p < 0.05 considered significant). Results: The majority of participants were aged 31–50 years. Among smokers, combined cigarette and hookah use was predominant, and most had a university-level education. Smokers exhibited significantly higher hemoglobin, hematocrit, and RBC levels compared to non-smokers (p < 0.001), while WBC counts were slightly lower. Platelet counts were modestly elevated in smokers (p < 0.05). These findings indicate that smoking induces systemic haematological changes, which may predispose individuals to cardiovascular and metabolic complications. Conclusion: Smoking significantly impacts key hematological parameters among adult males, reflecting early physiological stress and potential health risks. Routine monitoring of blood indices in smokers could facilitate early intervention and support public health strategies for smoking cessation.